Proses Kreatif Sampul Buku Komik Autobiografi Masmundari dan Damar Kurung untuk Mengubah Prilaku Pada Remaja - Muh. Widyan Ardani (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2018)
Who does not familiar with every aspect of old age the late mbah Masmundari the creator of the craft that resulted in concluding historic unique in the land of east java exactly in the regions gersik namely resin brackets. The music having influence the force that can make people just youth and this is he to his work especially small because the form of 6 simple visual and scratches a color that disiratkan by the mbah (Masmundari) was more of a naifisme decorative style. A book about visual autobiography creator resin brackets for the generation of young and young, because it has humanist values, religious, moral and, so that they know their values and culture that they have. It is hoped the autobiography about creator resin brackets this can solve problems expressed earlier by a writer. The experimental work on of recent days picks up the finding that autobiography about Masmundari and damar kurung is important element for the formation of a behavior in adolescents and can be a learning process that is ideal for children, because it could affect a stimulus a child to studies and observe deeper into questions of local tradition and those values are contained in it nevertheless that a work of the creation of the design of comic education which cannot yet be completely perfect because need great precision of making a structure to sustain the cability of between stories and its intended audience especially in east java regional because they are still under the manufacture and a preliminary sketch autobiography design about Masmundari and Damar kurung. Keywords: Damar Kurung, Autobiography, Cover Book